Trace Element Content of a Heavy Clay Soil from England Under Free and Poor Drainage - Yadav, J. S. P. (Indian Forester, 1964)
An investigation was undertaken to examine the trace-element content of a heavy clay soil under the conditions of poor and free drainage. Spectrographic methods were employed for the determination of trace elements. The results revealed that the drainage status had very little influence on the total content, but poor drainage caused an appreciable increase in the amount of ’available’ fraction of most minor elementas of all the elements studied, the highest percentage of availability due to poor drainage was noticed in the case of Cu, Co, Ni, and Pb. The data also suggest that only a small fraction of the total content is available at a particular time and there is no direct relationship between the total and ’available’ forms.